1977
DOI: 10.1073/pnas.74.4.1702
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity of a serum marker for hepatitis B: evidence that "e antigen" has the properties of an immunoglobulin.

Abstract: A family of antigens, referred to collectively as e antigen (eAg), has been detected in sera of some individuals with liver disease who test positive for hepatitis B surface antigen. Studies on eAg partially purified by affinity chromatography on insolubilized antiboies to eAg revealed the following: (i) (eAg). Though distinct from HBsAg in both immunologic and physicochemical properties (8), eAg is also specifically associated with HBV infections and appears to be a marker for the infectivity of HBsAg-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

1978
1978
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…3c) were also detected in sera. Neurath & Strick (1977) demonstrated that the pI of anti-HBe IgGs were heterogeneous, having the pI range from 5.8 to 10.2. Therefore, the heterogeneity in pI of IgG-associated HBeAg may result from the different number of IgG molecules which bind to HBeAg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3c) were also detected in sera. Neurath & Strick (1977) demonstrated that the pI of anti-HBe IgGs were heterogeneous, having the pI range from 5.8 to 10.2. Therefore, the heterogeneity in pI of IgG-associated HBeAg may result from the different number of IgG molecules which bind to HBeAg.…”
Section: Discussionmentioning
confidence: 99%
“…As for the IgG-associated HBeAgs, the earlier work of Neurath & Strick (1977) indicated that HBeAg, partially purified from the pooled serum of asymptomatic carriers, had the properties of human immunoglobulin, mainly of the IgG4 subclass. Fields et al (1978) and Weft et al (1979) have also shown that HBeAg might be closely associated with human serum IgG.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, IgGl and IgGB were equally affinitive to the placenta, but IgG4 was much less reactive. Neurath et al (10) reported that the subclass of IgG in molecules with HBeAg activity was IgG4. Weak affinity of IgG4 for the placenta, a large size of IgG-bound HBeAg, and inability for free HBeAg to pass the placenta would be among the factors responsible for the observed difference of HBeAg activity between maternal and cord sera.…”
Section: Discussionmentioning
confidence: 99%
“…Polystyrene beads (diam. 6 mm) were immersed in a solution of anti-HBc [IOO/~g IgG/ml in o.I M-tris (hydroxymethyl) aminomethane, pH 8.8] prepared from an anti-HBo-positive serum as described before (Neurath & Strick, 1977). After several hours at room temperature, the solution of anti-HBo was removed, the beads were washed several times with TS and then immersed in a solution of bovine haemoglobin (IO mg/ml in TS).…”
Section: Introductionmentioning
confidence: 99%
“…Isoelectric focusing was performed as described before (Neurath & Strick, 1977). HB~Ag and antibodies to HB~Ag (anti-HB,) were determined by radioimmunoassays using commercial reagents (Abbott Laboratories, North Chicago, Illinois).…”
Section: Introductionmentioning
confidence: 99%